Integrating Biophilic Design and Eco-Village Concepts for sustainable water tourism development: A case study of Bah Tio Eco-Village, Pematang Silampuyang Spring, Siantar District, Simalungun Regency, North Sumatra, Indonesia - Ina Triesna Budiani; Meisy Refina Lafenia Sitorus (Jurnal VORTEKS, 2026)
Indonesia’s spring-based water tourism possesses significant potential but faces challenges in unsustainable management, limited design innovation, and weak community linkages. This study aims to develop an integrated framework for Bah Tio Eco-Village, North Sumatra, by combining Biophilic Design and Eco-Village principles. Employing qualitative descriptive methods, data were collected via site observation, stakeholder interviews, and comparative analysis with regional and international cases. The framework operationalizes key biophilic patterns Visual Connection with Nature, Biomorphic Forms & Patterns, and Thermal & Airflow Variability within Eco-Village dimensions of ecological integrity, social empowerment, and mushroom-centered circular economy. Results demonstrate enhanced visitor restoration, environmental preservation, and inclusive local economic development. The novelty lies in translating biophilic spatial strategies into a place-based, spring-centered eco village model with low-impact engineering and community governance. This replicable model contributes to sustainable and regenerative water tourism in tropical agricultural landscapes.